The Neoclassical Model and the Welfare Costs of Selection - Fabrice Collard; Omar Licandro (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper embeds firm dynamics into the Neoclassical model and provides a simple framework to solve for the transitional dynamics of economies moving towards more selection. As in the Neoclassical model, markets are perfectly competitive, there is only one good and two production factors (capital and labor). At equilibrium, aggregate technology is Neoclassical, but the average quality of capital and the depreciation rate are both endogenous and positively related to selection. At steady state, output per capita and welfare both raise with selection. However, the selection process generates transitional welfare losses that may reduce in around 60% long term (consumption equivalent) welfare gains. The same property is shown to be true in a standard general equilibrium model with entry and fixed production costs.
Keywords: E13; E23; D60; O40; 330; firm dynamics and selection; neoclassical model; capital irreversibility; investment distortions; transitional dynamics; welfare gains